Indonesian State Law in its Historical Perspective and Development - Leliya Leliya; saeful ansori; siti maghfiroh (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The history of Indonesian constitutional law began in the Dutch colonial period when Indonesia was still called the Dutch East Indies. Then after Indonesia's independence in 1945, for the first time formed a constitution or Basic Law. The focus of the study in this study is to try to explain the development of Indonesian constitutional law from the Old Order era to reform. This is to find out how the history of the development of Indonesian constitutional law from time to time, especially from the beginning of independence to reformation. The method in this study is qualitative, with a historical approach. The data collection method used is the method of library research (library research). Then analyzed using the descriptive-analytic method. At the beginning of independence in 1945, Indonesia's constitutional law was contained in the 1945 Constitution. The 1945 Constitution described Indonesia as a unitary state with a president as the head of state as well as a democratic head of government. Besides that, under Soekarno's government, constitutional law was regulated in several constitutions, including the 1949 RIS constitution and the 1950 UUDS. And Soekarno's government at that time was known for its nationalist and anti-capitalist politics. The Suharto government was known for its authoritarian politics, political stability, and economic growth. Finally, during the reform period, after the fall of President Soeharto in 1998, Indonesia underwent significant political reforms. Constitutional law is regulated in the 1945 Constitution with several amendments which emphasize the principles of democracy, human rights, decentralization of government, and increased political participation. The history of the development of constitutional law in Indonesia in general shows quite dynamic developments and always follows changes according to political and socio-cultural developments in Indonesia.